Effectiveness of a Goldilocks Work intervention in childcare workers - A cluster-randomized controlled trial - Kathrine Greby Schmidt; Anders Fritz Lerche; Marie Raunkjær Christensen; Charlotte Lund Rasmussen; Leon Straker; Svend Erik Mathiassen; Andreas Holtermann (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: Poor cardiorespiratory fitness and health is common among childcare workers. We designed the `Goldilocks-games` according to the Goldilocks Work principle to provide high-intensity physical activity for childcare workers. We investigated the effectiveness of this Goldilocks Work intervention in increasing occupational high-intensity physical activity and improving work-related health. METHODS: In a two-arm cluster randomized trial, 16 childcare institutions with 142 workers were randomly allocated to either an 8-week Goldilocks Work intervention or a control group. The primary outcome was occupational time in high-intensity physical activity. Secondary outcomes were occupational time in active physical behaviors, heart rate during sleep, pain, physical exhaustion, energy at work, work productivity, and need for recovery. RESULTS: The intervention was successfully delivered and received. Both groups had a low amount of occupational high-intensity physical activity at baseline, and the intervention group reported playing the games 3.1 [standard deviation (SD) 1.5] times/week for a duration of 112.2 (SD 175.0) min/week. However, the intervention did not increase high-intensity physical activity or the secondary outcomes, except for energy at work, measured on a scale from 0-10, increasing 0.65 [95% confidence interval (CI) 0.08-1.21], and need for recovery, measured on a scale from 1-5, decreasing -0.32 (95% CI, -0.54- -0.09). CONCLUSION: The intervention was successfully delivered and received, but did not increase high-intensity physical activity. The intervention group increased their energy at work and decreased their need for recovery, but not the other health-related outcomes. Further research on how to design and implement health-promoting work environment interventions in childcare is needed.